Disappearing act: The Daniel J. Terra collection of American art (1971–2005). (17th December 2018) - Yahr, Jayme
Abstract: The American self-made businessman Daniel J. Terra (1911–1996) collected art as a testament to his patriotism and in an attempt to establish his cultural prowess. Between 1971 and his death in 1996, Terra amassed a collection of 605 paintings, works on paper, and sculpture, made possible by a small network of art dealers who aided Terra in his rapid transformation of the American art market. After a failed attempt to donate his collection to the Art Institute of Chicago, Terra created not one, but two museums in Illinois and one in France over the course of twelve years. Each Terra-backed museum struggled to find visitors, structures of support, and strategic vision while under his control. With the disappearance of each museum, the story of Terra's art collection became inexorably intertwined with concepts of value, identity, and the physical shift from private hobby to public endeavour.